Anticancer Effects of Sinocrassulosides VI/VII from Silene viscidula on HeLa Cells. (9th July 2017) - Chen, Hang; Ma, Qian; Xu, Wei; Li, Wan-Ming; Yuan, De-Zheng; Wu, Jia-Mei; Li, Yu-Shan; Fang, Jin
Abstract : Natural products are becoming increasingly important in chemoprevention and for cancer therapy. Silene viscidula (S. viscidula), a traditional Chinese herb, has long been used as an anti-inflammatory and neuroleptic agent. However, the anticancer activity of S. viscidula has remained unclear. In this study, 16 compounds were extracted from S. viscidula . Among those compounds, sinocrassulosides VI/VII, an inseparable isomer mixture, possess the strongest inhibitory activity on HeLa cells with the IC50 value of 2.37  μ M. Mechanism studies found that sinocrassulosides VI/VII downregulated the expression of cyclin D1 and decreased retinoblastoma (Rb) phosphorylation, which arrested HeLa cells in the G1 phase. Also, sinocrassulosides VI/VII could induce senescence via the upregulation of p16 and a significant increase of β -galactosidase ( β -gal) staining. Our results suggest that sinocrassulosides VI/VII may be a new therapeutic potential agent for cervical cancer. In addition, we explored the structure-activity relationships of three groups of the configurational isomer with similar chemical structure from S. viscidula . We first demonstrated that the length of the ester chains linked to the carboxyl group of the glucuronic acid residue could affect the potent cytotoxicity. This finding will open new avenues for developing effective anticancer compounds by modifying the components derived from plants in nature.